2006
DOI: 10.1002/prot.20905
|View full text |Cite
|
Sign up to set email alerts
|

Structural and thermodynamic consequences of removal of a conserved disulfide bond from equine β‐lactoglobulin

Abstract: A disulfide bond between cysteine 66 and cysteine 160 of equine beta-lactoglobulin was removed by substituting cysteine residues with alanine. This disulfide bond is conserved across the lipocalin family. The conformation and stability of the disulfide-deleted mutant protein was investigated by circular dichroism. The mutant protein assumes a native-like structure under physiological conditions and assumes a helix-rich molten globule structure at acid pH or at moderate concentrations of urea as the wild-type p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…C66A/C160A was expressed and purified as previously described (Yamada et al, 2006). Chemicals were of analytical grade from Nacalai Tesque or Wako Pure Chemical Industries (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…C66A/C160A was expressed and purified as previously described (Yamada et al, 2006). Chemicals were of analytical grade from Nacalai Tesque or Wako Pure Chemical Industries (Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of chloride ion, however, the molecular dimension and shape was close to that in the urea-unfolded state. Previously, we have shown that the helix content in the acid-denatured state increases with decreasing chloride-ion concentration [Yamada et al (2006). Proteins Struct.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…36 Refolded Gyuba was purified by DEAESepharose chromatography with a linear gradient of 0-350 mM NaCl in 50 mM Tris-HCl (pH ¼ 8.0). The fraction that contained Gyuba was further purified by gel-filtration chromatography (Sephacryl S-100 equilibrated with 5 mM NH 4 HCO 3 ) and then by QSepharose chromatography with a linear gradient of 0-500 mM NaCl in 20 mM PIPES (pH ¼ 7.0).…”
Section: Design Of the Gyuba Gene And Construction Of Its Expression mentioning
confidence: 99%